2013
DOI: 10.31028/ji.v8.i2.99-114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation and Cassava Peel Mulch on Soil Water Content and Pineapple Growth

Abstract: Irigasi pada tanaman nanas sangat penting karena mempengaruhi pertumbuhan dan produksi namun biayanya sangat mahal. Penelitian ini bertujuan untuk mengetahui pengaruh irigasi dan mulsa organik pada kadar air tanah dan pertumbuhan nanas. Penelitian ini dilakukan menggunakan perlakuan faktorial (5 x 2) dalam rancangan acak kelompok dengan tiga ulangan. Faktor pertama adalah panjang waktu irigasi (I), yang terdiri dari 5 waktu yaitu tanpa irigasi (I0), irigasi 1 bulan (I1), irigasi 2 bulan (I2), irigasi 3 bulan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…According to [8], the addition of irrigation water will greatly affect soil moisture which will further increase plant growth and development. [9] in their research stated that the addition of irrigation greatly affected the changes in soil water content which increased because it was one of the suppliers of water in the soil. The results of observations of the average soil moisture content showed that in the 3rd week the soil moisture content in all treatments experienced the highest average decrease, amounting to 28.13% from the previous (2nd week) 45.63%.…”
Section: Soil Moisture Contentmentioning
confidence: 99%
“…According to [8], the addition of irrigation water will greatly affect soil moisture which will further increase plant growth and development. [9] in their research stated that the addition of irrigation greatly affected the changes in soil water content which increased because it was one of the suppliers of water in the soil. The results of observations of the average soil moisture content showed that in the 3rd week the soil moisture content in all treatments experienced the highest average decrease, amounting to 28.13% from the previous (2nd week) 45.63%.…”
Section: Soil Moisture Contentmentioning
confidence: 99%
“…Pineapple apple is one of horticulture commodity from Indonesia which has high potential in international fruits trade. The other hand, irrigation on pineapple plants is very important because it affects the growth and production (Rahmat et al 2013). Azevedo et al (2007) Reported, evapotranspiration pineapple plant in vegetative phase reach 3.5mm/day and total water use in vegetative phase around 1421 mm for 270-330 day.…”
Section: Introductionmentioning
confidence: 99%